Identification of inadequate maternal progesterone concentrations in nulliparous dairy heifers and treatment with human chorionic gonadotrophin. (9th November 2013) - King, S. G.; Dobson, H.; Royal, M. D.; Christley, R. M.; Murray, R. D.; Routly, J. E.; Smith, R. F.; Mann, G. E.
Abstract : Plasma progesterone concentrations were estimated for 381 nulliparous dairy heifers from eight farms on days 4–6 after insemination. Heifers were synchronised using two treatments of prostaglandin F2α (PGF2α) 11 days apart. Alternate heifers were treated with 1500 IU human chorionic gonadotrophin (hCG) at the time of sampling, and the pregnancy status assessed ∼35 days after insemination. Heifers with no corpus luteum (CL; n‐30) at the second PGF2α had lower progesterone concentrations (P<0.001) and pregnancy rates (PR; P=0.001) compared with heifers with CL (n=351, defined as cyclic). The risk of no CL increased in heifers <15 months of age (OR=7.5, P<0.001) and with body condition score <2.5 (OR=4.5, P=0.001). Those with no CL were removed from further analysis. The 20 per cent cyclic control heifers with progesterone concentrations ≤2 ng/ml on days 4–6 had lower PRs compared with those with higher concentrations (42 per cent vs 64 per cent, OR=0.3, P=0.01). There was no overall effect of hCG on PR compared with controls (51 per cent vs 60 per cent, P=0.10). However, heifers with high progesterone on days 4–6 (>2 ng/ml) had a lower PR after treatment (51 per cent vs 64 per cent, OR=0.6, P=0.02). Heifers inseminated with sexed (n=18) compared with conventional (n=333) semen had a decreased PR (33 per cent vs 57 per cent, OR=0.2, P=0.01). This study demonstrates that higher plasma progesterone concentrations as early as days 4–6 after insemination have a positive effect on first insemination PR, but there was no beneficial effect of hCG treatment on these days in dairy heifers.